ABSORPTION VELOCITY OF GLUFOSINATE AND ITS EFFECTS ON WEEDS AND COTTON - Freitas e Silva, Ilca Puertas de [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP]; Silva, Josue Ferreira [UNESP]; Tropaldi, Leandro [UNESP]; Larissa, Giovanna [UNESP]; Gomes, Gimenes Cotrick [UNESP] (Colegio Postgraduados, 2016)
Glufosinate ammonium, an inhibitor of the enzyme glutamine synthetase (GS), is one of the most important herbicides for cotton cultivation and it is utilized for weed management in directed spray applications indicated for conventional cultivars. This study aimed to evaluate the absorption velocity of glufosinate ammonium and its effects on weed and cotton (Gossypium hirsutum L.) plants. The study was carried out in a greenhouse with the cotton cultivar FiberMax 910 and the weeds Brachiaria decumbens and Ipomoea grandifolia. The experimental design was completely randomized and treatments were: the herbicide glufosinate ammonium (0.4 kg a.i. ha(-1)); five periods before a simulated rain (times for absorption) (1, 3, 6, 24 and 48 h between herbicide application and simulated rain); a control without herbicide; and four repetitions per treatment. Plants were harvested 2 d after herbicide application to quantify their contents of ammonia, glutamine and glufosinate. Visual injury of plants was quantified at 1, 3, 6, 8 and 10 d after application (DAA) of glufosinate ammonium using a percentage scale for damages. Regression analyses were performed on the results and a standard error (by t test; p <= 0.05) was established for the means. Glufosinate ammonium absorption increased up to 24 h in cotton, and 48 h in B. decumbens and I. grandifolia. Despite the increase in glufosinate levels in 48 h without rain periods, the contents of ammonia were increased and glutamine was reduced between 1 and 6 h without rains. In addition, the three species presented severe injuries starting at 3 h without rain.
Keywords: Weeds; Gossypium hirsutum; herbicide; mode of action